DESIGNING THE BRANDING FOR ROMANO'S TRADITIONAL SAGON SNACK IN BANDUNG - Sausan; Siswanto, Riky Azharyandi; Nurbani, Sri (eProceedings of Art & Design, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in local economies. Romano, an MSME specializing in coconut Sagon, struggles with brand awareness, making it hard to attract new customers. This study explores the importance of branding and provides insight into Romano's current business state. Data was collected through interviews with Romano’s owner, observations comparing Romano with competitors, and questionnaires with over 100 respondents to gauge consumer preferences. The study used the Activities, Interests, and Opinions (AIO) Model to map the customer journey, SWOT analysis to assess Romano's market position, and a Comparison Matrix to evaluate brand identity. The findings show that branding significantly influences customer decision-making. Romano's current branding is inadequate and misaligned with its target audience's preferences. This research underscores the need for Romano to create a strong branding to attract more customers. Keywords: MSME, branding, Sagon